ANALISIS PENGARUH KUALITAS LAYANAN, HARGA DAN KEPUASAN TERHADAP LOYALITAS PASIEN RAWAT INAP DI RS. BHAKTI RAHAYU SURABAYA - Sumitro, Yanus; wahjono, wahjono (Universitas PGRI Adi Buana, 2018)
The research was conducted at the Surabaya Bhakti Rahayu Hospital. Study sample was 100 hospitalized patients. The results are: (1) no significant effect between service quality and satisfaction, (2) Rates of satisfaction is significantly affected, (3) quality of service is significantly affected loyalty (4) there was no significant effect between price and loyalty, (5) satisfaction is influenced significant loyalty. Based on our research, this suggests that patients should be more careful to avoid disappointment hospitalization. To the management should have a positive communication with patients when declining consumer confidence. And further research should be done continuously with similar time intervals to determine whether or not there is an increase in satisfaction, as a result of the increased performance of the services performed and prices that affect customer loyalty